Prompt engineering and creative pedagogical thinking: Insights from a qualitative study with teacher candidates - Akyildiz, Secil Tumen (Elsevier Sci Ltd, 2026)
This qualitative study explores how pre-service EFL teachers perceive and engage with prompt engineering as a tool to foster creative pedagogical thinking. Over the course of seven weeks, participants collaborated with the researcher to develop lesson materials using ChatGPT. The study draws on data collected through semi-structured interviews with ten participants and employs reflexive thematic analysis to interpret their experiences. Findings indicate that most teacher candidates transitioned from using simple prompts to designing more structured and purposeful ones, gradually developing both prompt literacy and confidence in AI-supported lesson planning. Three major themes emerged: conceptual understanding of prompt engineering, prompt design as a catalyst for creativity, and evolving skills through iterative practice. Participants highlighted the pedagogical benefits of AI in saving time, adapting content, and generating innovative ideas, though challenges such as evaluating AI output and formulating effective prompts were also noted. While the findings are context-specific, they suggest that prompt engineering-when supported by guided practice-can be a meaningful component in teacher education programs, contributing to the cultivation of digital literacy, reflective practice, and creative thinking in future educators.
Keywords: Prompt engineering; Creative pedagogical thinking; Pre-service teacher education